Loss of ubiquitin-specific peptidase 18 destabilizes 14-3-3ζ protein and represses lung cancer metastasis. Issue 1 (31st December 2022) - Chen, Zibo; Zheng, Lin; Chen, Yulong; Liu, Xiuxia; Kawakami, Masanori; Mustachio, Lisa Maria; Roszik, Jason; Ferry-Galow, Katherine V.; Parchment, Ralph E.; Liu, Xin; Andresson, Thorkell; Duncan, Gerard; et al.
ABSTRACT: Cancer metastasis is a major cause of cancer-related mortality. Strategies to reduce metastases are needed especially in lung cancer, the most common cause of cancer mortality. We previously reported increased ubiquitin-specific peptidase 18 (USP18) expression in lung and other cancers. Engineered reduction of USP18 expression repressed lung cancer growth and promoted apoptosis. This deubiquitinase (DUB) stabilized targeted proteins by removing the complex interferon-stimulated gene 15 (ISG15). This study explores if the loss of USP18 reduced lung cancer metastasis. USP18 knock-down in lung cancer cells was independently achieved using small hairpin RNAs (shRNAs) and small interfering RNAs (siRNAs). USP18 knock-down reduced lung cancer growth, wound-healing, migration, and invasion versus controls (P < .001) and markedly decreased murine lung cancer metastases (P < .001). Reverse Phase Protein Arrays (RPPAs) in shRNA knock-down lung cancer cells showed that 14-3-3ζ protein was regulated by loss of USP18. ISG15 complexed with 14-3-3ζ protein reducing its stability. Survival in lung adenocarcinomas (P < .0015) and other cancers was linked to elevated 14-3-3ζ expression as assessed by The Cancer Genome Atlas (TCGA). The findings were confirmed and extended using 14-3-3ζ immunohistochemical assays of human lung cancer arrays and syngeneic murine lung cancer metastasis models. A direct 14-3-3ζ role in controlling lung cancer metastasis came from engineered 14-3-3ζ knock-down in lung cancer cell lines and 14-3-3ζ rescue experiments that reversed migration and invasion inhibition. Findings presented here revealed that USP18 controlled metastasis by regulating 14-3-3ζ expression. These data provide a strong rationale for developing a USP18 inhibitor to combat metastases.